Bridging the Gaps of Clean Mobility and Transport through Engineering Interventions - Oyebode, Oluwadare Joshua (Journal of Sustainability and Environmental Management, 2022)
Transportation plays a significant role in sustainable development, civilization, industrialization and commercialization in many countries around the globe. This paper looked into bridging the gaps in clean mobility and transport through engineering interventions and other innovative ideas. Salient issues affecting clean mobility and an effective transport system were highlighted and possible solutions were suggested. The methodology includes a literature survey and consultation of environmental experts. A deeper understanding of the gaps between mobility and transportation management can provide insightful information into how cities must be structured. Clean mobility refers to all forms of transportation that do not require the use of fossil fuels exclusively. Mobility specializes in making ground-breaking solutions that enable mobility and industry to attain zero-emissions status. It was concluded that engineering interventions and other innovative ideas can be used to bridge the gaps in clean mobility and transport. Monitoring climate change and reduction of environmental pollution are very vital for the sustainable green environment in African urban communities. There is a need to strengthen digital advancements for integrated solutions in infrastructural development and transportation networks. Proper planning, adequate funding and sustainable development are very crucial for bridging the gap and attaining of a cleaner environment.